ANALISIS SEMANTIK KATA ZAWJ DALAM AL-QUR’AN - Marjiatun Hujaz; Nur Huda; Syihabudin Qalyubi (STAI AL-ANWAR SARANG, 2018)
This study aims to examines the meaning of zawj in al-Qur'an. This research is a qualitative research using descriptive-analysis method. The meaning of zawj in the Qur'an is very vareative. In the Koran with various derivations, the word zawj is 21 derivations contained in 72 verses of 43 surahs and is mentioned in 81 times. The researcher used the semantic analysis of al-Qur'an which was initiated by Toshihiko Izutsu who tried to address the world view of Qu'ran (weltanschauung) through semantic analysis of the vocabulary and key terms in the Qur’an. This research concludes that the basic meaning of the word zawj is something that is not singular or something that has an equivalent. Zawj can be interpreted as: a husband in the surah (al-Mujādalah [58]: 1;wife in the surah (al-Baqarah [2]: 35; a partner, namely Allah created all beings in pairs (az-Dzariyat [51]: 49;animals are male and female pairs (al-An'ām [6]: 143), plants (al-Syu'arā [367]: 7); and groups (al-Wāqi'ah [56]: 7. In the pre- Qur'anic, the word zawj is defined as a rug. In the Qur'anic period it is divided into two, namely Mecca and Medina. The Mecca period has a close meaning with the sign of the greatness of Allah and the pleasure that Allah gives. The Medina period contains the laws of separation. In the post-Qur'anic period, the word zawj describes gender equality, that men and women are the same components without being differentiated, so that there is a harmonious life in pairs.